2013
DOI: 10.1371/journal.pone.0064119
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Foot-and-Mouth Disease Virus Tropism Inferred from Differential Tissue Gene Expression

Abstract: Foot-and-mouth disease virus (FMDV) targets specific tissues for primary infection, secondary high-titer replication (e.g. foot and mouth where it causes typical vesicular lesions) and long-term persistence at some primary replication sites. Although integrin αVβ6 receptor has been identified as primary FMDV receptors in animals, their tissue distribution alone fails to explain these highly selective tropism-driven events. Thus, other molecular mechanisms must play roles in determining this tissue specificity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…This lack of evidence of cellular degeneration of FMDV-infected cells in carriers suggests a distinct mechanism in which infected cells survive and remain within the carrier's epithelium. These findings are consistent with previously published suggestion that in the carrier state, FMDV employs a distinct, non-cytolytic infection process which may be driven by alterations in cytokine signaling cascades and/or tissue specific decreased cell death mechanisms [3,53].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This lack of evidence of cellular degeneration of FMDV-infected cells in carriers suggests a distinct mechanism in which infected cells survive and remain within the carrier's epithelium. These findings are consistent with previously published suggestion that in the carrier state, FMDV employs a distinct, non-cytolytic infection process which may be driven by alterations in cytokine signaling cascades and/or tissue specific decreased cell death mechanisms [3,53].…”
Section: Discussionsupporting
confidence: 93%
“…However, the causality of this association remains undermined; specifically, one might consider whether 1) FMDV dysregulated the expression of these genes thus enabling the carrier state or 2) a subset of cattle are intrinsically poor producers of IFN and it is these animals that ultimately become carriers. Previous work describing gene expression in tissues with different FMDV tropism from non-infected cattle suggested that pharyngeal tissues are intrinsically poor type I and III IFN inducers and responders, and this might explain their susceptibility to both primary and persistent infection (Zhu et al 2013). The results of the current study are consistent with those findings.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations